Economic performance evaluation of process system design flexibility options under uncertainty: The case of hydrogen production plants with integrated membrane technology and CO2 capture. (6th April 2017) - Ma, Liang-Chih; Castro-Dominguez, Bernardo; Kazantzis, Nikolaos K.; Ma, Yi Hua
Highlights: Use of catalytic membrane reactors in hydrogen production (HP-CMR) is considered. An economic evaluation study of design flexibility options in HP-CMR is conducted. Flexibility options in the installation and operation of a CCS unit are considered. Sources of uncertainty are explicitly recognized through Monte-Carlo techniques. Potentially value-enhancing design flexibility options in HP-CMR are demonstrated. Abstract: A hydrogen production plant with integrated catalytic membrane reactor modules (HP-CMR) represents a new technology option with potentially enhanced environmental performance characteristics. Therefore, HP-CMR techno-economic performance in the presence of irreducible sources of uncertainty (market, regulatory) ought to be comprehensively evaluated in order to accelerate the realization of future demonstration plants. The present study introduces a systematic methodological framework allowing the economic value assessment of various flexibility options in the design and operation of an HP-CMR plant under the above uncertainty sources. The primary objective is to demonstrate the potentially value-enhancing prospects of design flexibility options that capture the inherent optionality element in managerial decision-making to actively respond to uncertainties as they are progressively resolved. A detailed Net Present Value (NPV)-based assessment framework is first developed within which the above sources of uncertainty are integrated through Monte Carlo techniques. Various constructional and operational flexibility options are introduced pertaining to the installation decision and operating mode choice of the carbon capture and sequestration (CCS) unit, and HP-CMR economic performance is comparatively assessed. Finally, under certain scenarios of regulatory action on CO2 emissions, it is demonstrated that quite appealing economic performance outcomes could emerge for HP-CMR plants once design flexibility is introduced.